The Ambit of modern commercial freedom in field of air transport - فاضل محمد عزت (Journal of Legal Sciences, 2020)
Liberalization of air transport depending on the freedom of companies to get investment and market access, including guarantee the Open Skies, and the transport must be based on equal opportunities in the field of capacity, and free competition. UAEs Constitution of 1971 adopted the freedom of economic activity, and social justice of the economy. The UAE legislator left the Conditions of services license to the specialist authority, It does not include establishment and preparation of airports or airstrips for civil aircrafts, as well as that the license does not include use or investment of airports. He also left setting rules of competition in the air transport sector to the federal authorities or local because of the nature of the federal regulatory system. While the Iraqi legislature is inclined to adopt modern economic fundamentals and to encourage investment, including the possibility of establishing the creation and preparation of airports or airstrips for civil aircraft, use or investment, as well as the competition systems are subject under a central law. The UAE law established General Authority of Civil Aviation, which considered as an independent body to contribute to the implementation of the Civil Aviation Act. While Iraqi legislator did not establish an independent body.